Medial subtalar dislocation without the presence of fracture. Case report - Largo González, Jorge Andres; Estrada Cely, Camilo Andres (Revista Colombiana de Ortopedia y Traumatología, 2016)
The case is presented of a 33-year-old patient admitted to the emergency department with a medial subtalar dislocation of the heel without the presence of an associated fracture. Treatment consisted of closed reduction and posterior splint immobilisation for 4 weeks, with a satisfactory clinical and radiological outcome after three months of follow up.